METODE ERRONEOUS EXAMPLE (CONTOH YANG KELIRU) PADA PEMBELAJARAN MATEMATIKA DI PERGURUAN TINGGI - Nur Baiti Nasution; Dewi Mardhiyana (Absis: Mathematics Education Journal, 2021)
Students errors are actually provide resources for teaching. Using students error, lecturer can emphasized certain concept while teaching, especially those concepts which make students confused. One of the teaching method that use students error is erroneous example. In this article, we developed a certain task using erroenous example method. The task consists of 10 question. Each question is made to tackle students understanding about a concept that is often mistaken by students. For each question, we give a correct/incorrect worked example, then students are asked to find the mistakes (if it is incorrect) or justify the steps (if it is correct). This study is a descriptive qualitative study that aims to describe the task and students response after doing the task. The method of collecting data was using observation, documentation, and interview. The results shows us that erroneous example task can be categorized difficult for students. However, it is also proved that it can be used to supporting students mathematics communication.